Assoreamento em densas redes de reservatórios: o caso da bacia hidrográfica da barragem Pereira de Miranda, Ce. - Lira, Daniely Lidiany Costa (2012)
The present study aims at analyzing the impacts of the dense reservoir network of the Pereira de Miranda catchment in its sediment yield and water storage capacity of the system. The studied area is located in the Brazilian Semiarid region, in the State of Ceará, with an area of approximately 3230 km2. It has an average annual rainfall of 854 mm and an annual potential evaporation of 1464 mm. The predominant soil and vegetation type are luvissolo and open shrub caatinga. Satellite imageries from wet years were used to identify the reservoirs of the catchment. Erosion units were identified derived from map overlay of the parameters of the Universal Soil Loss Equation (USLE), which enables the estimation of sediment yield and the identification of areas with high sediment production. A simplified model was used to simulate the sediment routing through the dense reservoir network of the basin. For the estimation of sedimentation at the Pereira de Miranda Reservoir, different scenarios of the system structure were considered. A mean erosion rate of 59 t.ha-1.year-1 was estimated for the basin, in which 42% of the basin area presents a moderate degree of erosion. According to the model, silting of the Pereira de Miranda reservoir may vary from 1.1 to 2.6 %.decade-1, depending on the scenario considered. One may observe that upstream reservoirs are able to retain until 58% of the sediments that would reach the Pereira de Miranda reservoir. The very small reservoirs, with storage capacity below 100,000 m³, are able to retain almost 8% of the generated sediments, although they represent just 1.83% of the system water storage capacity. Sensitivity analysis shows that the sediment retention capacity of the upstream reservoirs may vary from 20 to 58%, depending on the system structure concerning the presence of upstream reservoirs from different size classes. One may still conclude that the reduction rate of water storage capacity at the system as a function of reservoir siltation is relatively larger then that observed for the Pereira de Miranda reservoir, due to the upstream sediment retention.